Gene expression changes in mononuclear cells in patients with metabolic syndrome after acute intake of phenol-rich virgin olive oil - Camargo, Antonio; Ruano, Juan; Fernandez, Juan M; Parnell, Laurence D; Jimenez, Anabel; Santos-Gonzalez, Monica; Marin, Carmen; Perez-Martinez, Pablo; Uceda, Marino; Lopez-Miranda, Jose; Perez-Jimenez, Francisco (BMC genomics, 2010)
Previous studies have shown that acute intake of high-phenol virgin olive oil reduces pro-inflammatory, pro-oxidant and pro-thrombotic markers compared with low phenols virgin olive oil, but it still remains unclear whether effects attributed to its phenolic fraction are exerted at transcriptional level in vivo. To achieve this goal, we aimed at identifying expression changes in genes which could be mediated by virgin olive oil phenol compounds in the human. Postprandial gene expression microarray analysis was performed on peripheral blood mononuclear cells during postprandial period. Two virgin olive oil-based breakfasts with high (398 ppm) and low (70 ppm) content of phenolic compounds were administered to 20 patients suffering from metabolic syndrome following a double-blinded, randomized, crossover design. To eliminate the potential effect that might exist in their usual dietary habits, all subjects followed a similar low-fat, carbohydrate rich diet during the study period. Microarray analysis identified 98 differentially expressed genes (79 underexpressed and 19 overexpressed) when comparing the intake of phenol-rich olive oil with low-phenol olive oil. Many of these genes seem linked to obesity, dyslipemia and type 2 diabetes mellitus. Among these, several genes seem involved in inflammatory processes mediated by transcription factor NF-kappaB, activator protein-1 transcription factor complex AP-1, cytokines, mitogen-activated protein kinases MAPKs or arachidonic acid pathways. This study shows that intake of virgin olive oil based breakfast, which is rich in phenol compounds is able to repress in vivo expression of several pro-inflammatory genes, thereby switching activity of peripheral blood mononuclear cells to a less deleterious inflammatory profile. These results provide at least a partial molecular basis for reduced risk of cardiovascular disease observed in Mediterranean countries, where virgin olive oil represents a main source of dietary fat. Admittedly, other lifestyle factors are also likely to contribute to lowered risk of cardiovascular disease in this region.